EMOTIONAL WELL–BEING IN THE CLASSROOM FOR SUPPORTIVE LEARNING ENVIRONMENT (International Journal of Food and Nutritional Sciences, 2022)
The article on emotional well-being in the classroom highlights the essence of students’ participation positively. The author voices out the varied factors to be considered to bring out the salient features of emotional well-being in the classroom. Moreover, the article pinpoints the duties of educators, management, parents, and the environment in which they live. The author reviews it on emotional concepts like thoughts, feelings, empathy, gratitude, understanding, sharing, etc., to emphasize that students' life is indeed a blessing. Emotional well-being does not stop with mental wellness but also with physical entities. The article focuses on nutrition and dietetics, yoga and meditation, a fresh atmosphere and a serene environment for wonderful physical growth. If both physical and mental wellness work together, the student's level of intelligence reaches the pinnacle of success. Finally, the author has also pinpointed the challenges if the students fail to promote, concluding the positivity behind the emotional well-being in the classroom. Thus, the student's role is to develop into a pedestal of glory on the altar of emotional well-being through the connoisseurship of educators, parents and society.